Response of beach-nesting American Oystercatchers to off-road vehicles: An experimental approach reveals physiological nuances and decreased nest attendance. (6th December 2017) - Felton, Shilo K.; Pollock, Kenneth H.; Simons, Theodore R.
Abstract: Shorebird populations face increasing challenges as rising sea levels and growing human populations constrain their breeding habitats. On recreational beaches, the nesting season often coincides with a season of high visitor use, increasing the potential for conflict, which may negatively influence beach-nesting shorebird species. We designed a field experiment to study the responses of nesting American Oystercatchers ( Haematopus palliatus ) to off-road passenger vehicles (ORVs) at Cape Hatteras and Cape Lookout National Seashores in North Carolina, USA. We used continuous video and heart rate recordings to assess changes in the behavior and physiology of incubating oystercatchers. We conducted driving experiments affecting 7 nesting pairs in 2014 and 19 nesting pairs in 2015, between April and July of each year. Experimental treatments were repeated throughout the incubation period for each nest. Although responses were highly variable within and among pairs, paired randomized permutation tests indicated that, overall, oystercatcher pairs spent a greater proportion of time with their heads up and exhibited slower heart rates during driving treatments. Pairs also left their nests more frequently and attended their nests for a lower proportion of time during driving treatments, although these responses diminished over time. Higher nest attendance and lower departure rates late in incubation may have reflected a stronger attachment to nests closer to hatching or habituation to the driving treatment, although individuals continued to exhibit physiological responses to passing vehicles throughout incubation. Beach-nesting birds may benefit from reduced vehicle traffic at their nesting sites, allowing parents to spend more time attending the nest and less time on defensive behaviors.